1973
DOI: 10.1515/botm.1973.16.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Carbon Metabolism in Marine Algae

Abstract: Products of short term and one hour light fixation of 14 CO 2 in marine algal members like Ulva /aftaea, Sargastum ilicifolittm, Enteromarpha tnbnlosa t Spbaeelaria sp., Padina tetraslromatica and Cbaetomorpha media were investigated. It was found that aspartate is the major initial product of 14 CO 2 incorporation. Besides aspartate there is a significant incorporation in the PEP-PGA fraction. These findings indicate that HSK pathway is operative in the marine algae. Label in PEP-PGA fraction is indicative of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 20 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Carbonic anhydrases, which catalyse the CO2/HCO3 equilibtiurn and, therefore, facilitate the net transport of DIC to the location of active photosynthesis, are found in btown algae with extracellular and intracellular activities (e,g, Giordano & Maberly 1989;Surif & Raven 1989;Haglund et al 1992), In a nutnber of the larger brown algae ftom the Fucales and Laminariales, highly active dark fixation of CO2 via /}-carboxylation has been shown (see Kremer 1981 a,b;Sancho et al 1989) and high activities of a phosphoenolpyt uvate earboxykinase (PEPCK) have been docutnented (Akazawa, Ikawa & Nisizawa 1972;Kremer 198la,b), High short-term fixation of CO2 into aspatlate was atttibuted initially to a rnetabolistn sitnilar to that of higher C4 plants (Karekar & Joshi 1973;Joshi et al 1974), However, this hypothesis was refuted strongly by Kremer and Kuppers (1977) and PEPCK was later suggested to have a pritnaiily anaplerotic function associated with the tnobilization of the storage metabolite tnannitol (Kremer 1981a). However, the allegedly lower degtee of inhibition of photosynthesis by O2 in brown algae than in the red and green algae (investigated in the presence of 1 % CO2!)…”
Section: Introductionmentioning
confidence: 99%
“…Carbonic anhydrases, which catalyse the CO2/HCO3 equilibtiurn and, therefore, facilitate the net transport of DIC to the location of active photosynthesis, are found in btown algae with extracellular and intracellular activities (e,g, Giordano & Maberly 1989;Surif & Raven 1989;Haglund et al 1992), In a nutnber of the larger brown algae ftom the Fucales and Laminariales, highly active dark fixation of CO2 via /}-carboxylation has been shown (see Kremer 1981 a,b;Sancho et al 1989) and high activities of a phosphoenolpyt uvate earboxykinase (PEPCK) have been docutnented (Akazawa, Ikawa & Nisizawa 1972;Kremer 198la,b), High short-term fixation of CO2 into aspatlate was atttibuted initially to a rnetabolistn sitnilar to that of higher C4 plants (Karekar & Joshi 1973;Joshi et al 1974), However, this hypothesis was refuted strongly by Kremer and Kuppers (1977) and PEPCK was later suggested to have a pritnaiily anaplerotic function associated with the tnobilization of the storage metabolite tnannitol (Kremer 1981a). However, the allegedly lower degtee of inhibition of photosynthesis by O2 in brown algae than in the red and green algae (investigated in the presence of 1 % CO2!)…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a significant fractioti of carbon fixation in Ulva is mediated by a C4 pathway (Katekar & Joshi, 1973), the efftcient accessory pathway present in some terrestrial plants. Ulva has been shown to accumulate labelled aspartic acid after short periods of photosynthesis in '•^CO2 (Patil & Joshi, 1970) and the alga also has been shown to have an active //-carboxylase (Karekar & Joshi 1973), However, the kinetic characteristics of the Pcarboxylase in Ulva have not been examined and the presence of other necessary enzytnes of the C4 pathway has not been established, so that the operation of such a pathway in this alga is questionable. In other algae, notably the blue-green algae, where aspartate is a major itiitial labelled product of '*CO2 fixation, and which also have high activities of ^-carboxylases, the operation of a C4 accessory pathway has unequivocally been ruled out (Coletnan & Coltnan, 1981;Feuillade, Feuillade & Jolivet, 1982).…”
mentioning
confidence: 99%
“…Ulva has been shown to accumulate labelled aspartic acid after short periods of photosynthesis in '•^CO2 (Patil & Joshi, 1970) and the alga also has been shown to have an active //-carboxylase (Karekar & Joshi 1973), However, the kinetic characteristics of the Pcarboxylase in Ulva have not been examined and the presence of other necessary enzytnes of the C4 pathway has not been established, so that the operation of such a pathway in this alga is questionable. In other algae, notably the blue-green algae, where aspartate is a major itiitial labelled product of '*CO2 fixation, and which also have high activities of ^-carboxylases, the operation of a C4 accessory pathway has unequivocally been ruled out (Coletnan & Coltnan, 1981;Feuillade, Feuillade & Jolivet, 1982).…”
mentioning
confidence: 99%